Patterns of anti-osteoporosis medication use among women at high risk of fracture: findings from the Global Longitudinal Study of Osteoporosis in Women (GLOW). - Stephen Gehlbach (Public Library of Science (PLoS), 2013)
Objective To assess patterns of anti-osteoporosis medication (AOM) use over 3 years among women at high risk of major fracture. Methods The GLOW registry follows a cohort of more than 40,000 women aged ≥ 55 from 615 primary care practices in 10 countries. Self-administered surveys (baseline, 12, 24, and 36 months) collected data on patient characteristics, perception of fracture risk, and AOM use. FRAX scores were calculated from the baseline surveys and women classified as high risk if their FRAX 10-year probability of major fracture was ≥ 20%. Results A total of 5774 women were classified as at high risk and had complete data over 3 years. At baseline, 2271 (39%) reported receiving AOM, 739 (13%) reported prior but not current use, and 2764 (48%) said they had never used AOM. Over 3 years, 85% of baseline non-users continued as non-users and 15% initiated AOM; among baseline users, 49% continued the same medication class, 29% stopped AOM, and 12% switched. Women who stopped AOM were less likely to self-report osteoporosis (HR 0.56, 95% CI 0.42-0.75) than women who continued AOM. Compared with non-users who did not begin treatment, women initiating AOM were more likely to report a diagnosis of osteoporosis (HR 11.3, 95% CI 8.2-15.5) or osteopenia (HR 4.1, 95% CI 2.9-5.7) and be very concerned about osteoporosis (HR 1.9, 95% CI 1.3-2.8). Conclusions Less than 40% of women at high risk of fracture reported taking AOM. Women who stopped AOM were less likely to believe they have osteoporosis. Women who initiated treatment appeared motivated primarily by a diagnosis of osteoporosis or osteopenia and concern about the condition.